Executive Committee Minutes 2014-09-18 - Academic Senate:::::::::
Agenda Approved. Minutes of 9/4/14 approved. Chair Report. Provost Report. Vice Chair Report. Input on new smoking policy for Senate approved for Senate agenda. Vice President of Administration & Finance Report. Edited Sustainability Executive Committee Vision, Mission and Goals statement approved for second reading at Senate. Vice President of Student Affairs Report. EPC Report. Clarification of the Charge that EPC assemble certificate materials for the Senate. FSAC Report. SAC Report. CFA Report. Associated Student Report. Request for feedback from Senates on Student Success Fee. Senate Agenda. Good of the Order